Leopard population density and community attitudes towards leopards in and around Debshan Ranch, Shangani, Zimbabwe - Nyoni, Phumuzile (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2016)
Leopards (Panthera pardus) are regarded as one of the most resilient large carnivore species in the world and can persist in human dominated landscapes, areas with low prey availability nd highly fragmented habitats. However, recent evidence across much of their range reveals declining populations. In Zimbabwe, 500 Convention for the International Trade in Endangered Species (CITES) export tags are available annually for leopards as hunting trophies, despite limited accurate data on the leopard populations of the country. Moreover, when coupled with the massive land conversions under the controversial National Land Reform Programme (NLRP), leopard populations in Zimbabwe are in dire need of assessment. My study was conducted on Debshan ranch, Shangani, Zimbabwe, which is a commercial cattle (Bos indicus) ranch but also supports a high diversity of indigenous wildlife including an apparently healthy leopard population. However, the NLRP has resulted in an increase in small-holder subsistence farming communities around the ranch (the land was previously privately owned and divided into larger sub-units). This change in land-use means that both human and livestock densities have increased and the potential for human leopard conflict has increased. I estimated the leopard population density of the ranch and assessed community attitudes towards leopards in the communities surrounding the ranch. To estimate population densities, I performed spoor counts and conducted a camera trapping survey. Questionnaire interviews were used to assess community attitudes. My spoor counts provided a leopard density estimate of 13.57 leopards/100km2 compared to the camera trapping estimate of between 2.0 and 6.9 leopards/100km2. Although the high density estimate derived from the spoor counts is possible for Debshan because leopards are the apex predators and are adequately protected, potential edge effects are not yet fully understood. Thus, the more conservative estimate of 2.0 leopards/100km2, derived from the camera trapping survey, is probably more appropriate. Attitudes towards predators amongst respondents surrounding Debshan (n = 140) were neither too negative nor positive, attitude index had a mean score of 1.7 Â± 3.8 (range: -7 "“ 10). No single predictor variable used in my analysis was able to adequately explain why the communities held these negative views. However, livestock losses were repeatedly listed by respondents as being one of the main reasons for their lack of tolerance towards predators. The density estimate of 2.0 leopards/100km2 translates to a population of 9 "“ 26 leopards within Debshan ranch. This density estimate is too low considering the habitat type at Debshan ranch but should be interpreted with caution as it lacks fundamental elements like age and sex ratio. Moreover, the interaction of the leopard population with the surrounding communities is currently unclear. As a precautionary measure, I recommended reducing the annual hunting quota for Debshan from five to one leopard. Future work should aim to improve the attitudes of the surrounding communities to secure broader landscapes for leopard conservation while also reconciling density estimates to fully understand the leopard population of the region.
Keywords: Uncatalogued